Nanostructured sonophotocatalysts for spatially controlled inertial cavitation towards energy-efficient sonochemistry - Jonnalagadda, Umesh Sai (2023)
Catalytic nanomaterials have been demonstrated to enhance sonochemical processing through interactions with inertial cavitation events. Typically, sonochemistry generates inertial cavitation events directly from the solvent, which results in spatially uncontrolled cavitation events with limited interaction with the catalytic active site. These high intensity acoustic fields also result in thermal effects and side reactions, which may further influence chemical yields and selectivity. Herein, we report on ultrasound-responsive structured AuPd/TiO2 open nanoshells (TONs) to surface-stabilize gas bubbles for promoting cavitation events in the vicinity of catalytic active site. These exogenous bubbles trapped on catalytic active sites readily cavitate to produce free radicals for chemical reactions. Our findings indicate a positive trend between cavitation and benzaldehyde production in the presence of our AuPd/TONs. In contrast, nanostructures without gas-stabilization demonstrate reduced sonochemical conversion, suggesting the catalytic potential of nanostructuring photocatalytic materials to function as both cavitation agents and photo-oxidative catalysts, or photocatalytic nanostructure (PCN).